Answer:
x=3, y=7
x=-2, y=2
Explanation:
System of Equations
We have the following equations:
![y=-x^2+2x+10](https://img.qammunity.org/2021/formulas/mathematics/college/e5yf249h0u3dn3tfmfnzp3nkea7wdl14he.png)
![y=x+4](https://img.qammunity.org/2021/formulas/mathematics/middle-school/8tth4tmyyqhbacvw6xcbvm9t5gjdxjtg5o.png)
We'll solve it by substitution. Since the second equation is already solved for y, we use that expression and substitute into the first equation:
![x+4=-x^2+2x+10](https://img.qammunity.org/2021/formulas/mathematics/college/l20z7xpuia2kbpx0gj71dp1uwm1x6w6xa6.png)
Since this is a quadratic equation, it's convenient to have all terms to one side:
![x+4+x^2-2x-10=0](https://img.qammunity.org/2021/formulas/mathematics/college/4imr44nyc4lkrpfrlp6zly9c2e740wptyc.png)
Simplifying and reordering:
![x^2-x-6=0](https://img.qammunity.org/2021/formulas/mathematics/high-school/132rboduvig5kb5hdcumslpm26ziif6kxl.png)
Factoring:
![(x-3)(x+2)=0](https://img.qammunity.org/2021/formulas/mathematics/high-school/jgvjheqcfdd8wboxj89l9opg9f87a5gwba.png)
Solving:
x=3, x=-2
Those yield to two solutions for y:
y=x+4
y=7, y=2
The solutions of the system are:
x=3, y=7
x=-2, y=2